THE EVALUATION OF IRAQI PUREBRED ARAB HORSES OVER 12 YEARS - Al- khazraji, Sinan A. (The Iraqi Journal of Veterinary Medicine, 2021)
Changes in the exterior purebred Arab horses during the last 12 years have been analyzed. Measurements with regard to the exterior were made on the presently living 238 horses from Baghdad, Nenava and Dialla. The exterior of purebred Arab horses has not been found principally changed: only the length of trunk has become a little longer in stallion and the girths circumference width of chest increased while in mares the length of trunk has become a little shorter and the girths circumference width of chest decreased. Nowadays, the living Iraqi purebred Arab horses present leveled type of horses with harmonious conformation. It seems that a stable.